The Relationship Between Body Image and Confidence In Vocational High School Teenage Girls: Hubungan Antara Body Image Dengan Kepercayaan Diri Pada Remaja Putri Sekolah Menengah Kejuruan - Anggie Yuliani Pertiwi; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the phenomenon of adolescent girls experiencing low self-confidence, and aims to determine the relationship between body image and self-confidence in adolescent girls at SMK PGRI2 Sidoarjo. This study uses a quantitative methodology with a correlational approach and uses a psychological scale measuring instrument, namely the self-confidence scale and body image scale. The sample in this study was 191 adolescent girls from 413 female adolescent population who were taken using stratified random sampling technique, namely sampling based on a level (strata) in population members. Members of the population are divided into several levels (stratification) based on the characters that exist in the population. Data analysis was carried out using the Pearson correlation technique using the SPSS 17 for windows program. The results showed that there was a correlation of 0.444 with a significance of 0.000 and an R Square score of 0.197, which means that the hypothesis is accepted. There is a positive relationship between body image and self-confidence, and the effective contribution of body image affects self-confidence. 19.7%